Antimicrobial Properties of Palladium and Platinum Nanoparticles: A New Tool for Combating Food-Borne Pathogens - Chlumsky, Ondrej; Purkrtova, Sabina; Michova, Hana; Sykorova, Hana; Slepicka, Petr; Fajstavr, Dominik; Ulbrich, Pavel; Viktorova, Jitka; Demnerova, Katerina (International journal of molecular sciences, 2021)
Although some metallic nanoparticles (NPs) are commonly used in the food processing plants as nanomaterials for food packaging, or as coatings on the food handling equipment, little is known about antimicrobial properties of palladium (PdNPs) and platinum (PtNPs) nanoparticles and their potential use in the food industry. In this study, common food-borne pathogens Salmonella enterica Infantis, Escherichia coli, Listeria monocytogenes and Staphylococcus aureus were tested. Both NPs reduced viable cells with the log10 CFU reduction of 0.3-2.4 (PdNPs) and 0.8-2.0 (PtNPs), average inhibitory rates of 55.2-99% for PdNPs and of 83.8-99% for PtNPs. However, both NPs seemed to be less effective for biofilm formation and its reduction. The most effective concentrations were evaluated to be 22.25-44.5 mg/L for PdNPs and 50.5-101 mg/L for PtNPs. Furthermore, the interactions of tested NPs with bacterial cell were visualized by transmission electron microscopy (TEM). TEM visualization confirmed that NPs entered bacteria and caused direct damage of the cell walls, which resulted in bacterial disruption. The in vitro cytotoxicity of individual NPs was determined in primary human renal tubular epithelial cells (HRTECs), human keratinocytes (HaCat), human dermal fibroblasts (HDFs), human epithelial kidney cells (HEK 293), and primary human coronary artery endothelial cells (HCAECs). Due to their antimicrobial properties on bacterial cells and no acute cytotoxicity, both types of NPs could potentially fight food-borne pathogens.
Keywords: Foodborne Diseases; Humans; Food Microbiology; Palladium; platina; lidé; fibroblasty; Platinum; potravinářská mikrobiologie; antibakteriální látky; ledviny; Metal Nanoparticles; kovové nanočástice; Cells, Cultured; Fibroblasts; palladium; nemoci přenášené potravou; Bacteria; kultivované buňky; Anti-Bacterial Agents; Kidney